2017
DOI: 10.1002/mabi.201700201
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Dual‐Functional Hydrogel Using RGD and Anti‐VEGF Aptamer

Abstract: Synthetic molecular libraries hold great potential to advance the biomaterial development. However, little effort is made to integrate molecules with molecular recognition abilities selected from different libraries into a single biomolecular material. The purpose of this work is to incorporate peptides and nucleic acid aptamers into a porous hydrogel to develop a dual-functional biomaterial. The data show that an anti-integrin peptide can promote the attachment and growth of endothelial cells in a 3D porous p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 60 publications
1
31
0
Order By: Relevance
“…In fact, unlike mammalian polysaccharides such as hyaluronan, a glycosaminoglycan present in the extracellular matrix (ECM) that intrinsically contains functional domains (e.g., cell receptors such as CD44) (Misra et al, 2015 ), alginate lacks the ability to specifically interact with mammalian cells. To address this, chemical modifications to incorporate cell instructive/responsive moieties in otherwise “bioinert” polymers have been widely performed both in alginate and in several other natural or artificial polymers (Bidarra et al, 2010 ; Neves et al, 2015 ; Heo et al, 2017 ; Zhao et al, 2017 ; Kudva et al, 2018 ; Pereira et al, 2018a , b ). These “biofunctionalizations” can thus be designed to confer key biological features, like cell adhesiveness (Neves et al, 2015 ; Zhao et al, 2017 ; Kudva et al, 2018 ) or sensitivity to proteolytic degradation (Fonseca et al, 2011 ; Pereira et al, 2018b ), in polymers that despite being biocompatible are inert, non-fouling or non-adhesive materials ( Figure 3 ).…”
Section: Biofunctionalization Of Alginate Hydrogels With Cell Instrucmentioning
confidence: 99%
“…In fact, unlike mammalian polysaccharides such as hyaluronan, a glycosaminoglycan present in the extracellular matrix (ECM) that intrinsically contains functional domains (e.g., cell receptors such as CD44) (Misra et al, 2015 ), alginate lacks the ability to specifically interact with mammalian cells. To address this, chemical modifications to incorporate cell instructive/responsive moieties in otherwise “bioinert” polymers have been widely performed both in alginate and in several other natural or artificial polymers (Bidarra et al, 2010 ; Neves et al, 2015 ; Heo et al, 2017 ; Zhao et al, 2017 ; Kudva et al, 2018 ; Pereira et al, 2018a , b ). These “biofunctionalizations” can thus be designed to confer key biological features, like cell adhesiveness (Neves et al, 2015 ; Zhao et al, 2017 ; Kudva et al, 2018 ) or sensitivity to proteolytic degradation (Fonseca et al, 2011 ; Pereira et al, 2018b ), in polymers that despite being biocompatible are inert, non-fouling or non-adhesive materials ( Figure 3 ).…”
Section: Biofunctionalization Of Alginate Hydrogels With Cell Instrucmentioning
confidence: 99%
“…Therefore, they hold great promise for various diagnostic and therapeutic applications such as molecular imaging, disease diagnosis, drug development, and targeted delivery . In particular, Wang and coworkers demonstrated that when conjugated to hydrogel network, DNA aptamers mediated specific binding and release of proteins and cells . DNA aptamers are identified from random libraries of 10 12 to 10 16 oligonucleotides by an in vitro iterative selection process called systematic evolution of ligands by exponential enrichment (SELEX), which eliminates the need for sophisticated design of binding units.…”
Section: Methodsmentioning
confidence: 99%
“…The group of Wang, in particular, has developed several systems for stable retention and complementary strand-triggered release of the captured protein. [156][157][158][159][160]163,164] PEG diacrylate gels have been used as base materials for most of these works, serving as controllable synthetic hydrogel platforms which can be readily modified with the aptamers. The authors began by developing a superporous material using free radical polymerization coupled with gas foaming, with the goal of attaining high uptake and loading of target molecules, as well as allowing space for cell migration and transport of nutrients and oxygen.…”
Section: Selective Ligands For Gf Capturementioning
confidence: 99%